Evaluation of the effects of different forms of periodontal diseases on quality of life with OHIP‐14 and SF‐36 questionnaires: A cross‐sectional study. Issue 4 (9th June 2019) - Ustaoğlu, Gülbahar; Göller Bulut, Duygu; Gümüş, Kerem Çağlar; Ankarali, Handan
Abstract: Objectives: To investigate the effect of generalized aggressive periodontitis (GAP), generalized chronic periodontitis (GCP) and gingivitis (G) on oral health‐related quality of life (OHRQoL) with Oral Health Impact Profile‐14 (OHIP‐14) and Short Form‐36 (SF‐36) questionnaires. Methods: One hundred GAP patients, 114 GCP and 109 G patients were included in the study. Age, gender, number of missing teeth, probing depth (PD), bleeding on probing (BOP), plaque index (PI) and clinical attachment level (CAL) of patients were recorded. The Turkish versions of OHIP‐14 and SF‐36 questionnaires were filled before any medication and dental treatment were approved. The one‐way ANOVA test was used to compare three groups. Results: Generalized aggressive periodontitis and GCP groups were similar to each other ( P > 0.05) in most subscales except functional limitation and social disability of the OHIP‐14 questionnaire ( P = 0.034 and P = 0.018, respectively); conversely, there was no statistically difference between GAP and G groups in functional limitation and social disability subscales ( P = 0.856 and P = 0.242, respectively). GAP group gave higher scores than GCP group in all subscales of SF‐36 ( P < 0.05). There was a negative correlation between OHIP‐14 and SF‐36 subscale scores in all groups. Conclusion: Study findings indicate that different forms of periodontal disease have different effects on quality of life of patients when measured by OHIP‐14 and SF‐36. Patients with GCP and GAP had poorer OHRQoL than G patients.